Six ways to get a grip on developing reflexivity statements - Heather Braund; Jennifer Turnnidge; Nicholas Cofie; Oluwatoyosi Kuforiji; Sarah Greco; Amber Hastings-Truelove; Shannon Hill; Nancy Dalgarno (Canadian Medical Education Journal)
Qualitative researchers have underscored the value and importance of being reflexive in the research process, yet existing guidelines or checklists on how to practically address reflexivity are often scant and scattered across studies. In this scholarly perspective, we review, analyse, and present an overview of conceptions of reflexivity. Further, we offer practical guidelines for addressing and developing reflexivity statements in qualitative research. We describe reflexivity as both a concept and a deliberate ongoing process that requires a certain level of researcher consciousness, reflection, introspection, self-awareness, and an analytic attention to the researcher's role in the research process at all stages. We highlight the notion that reflexivity offers researchers an opportunity to examine potential assumptions, through the continuous process of questioning, examining, accepting, and articulating our attitudes, assumptions, perspectives, and roles. We present six recommendations to promote dialogue on the practice of reflexivity among researchers from various ontological and epistemological communities and encourage them to develop their own reflexivity practices.